Redistribution of inhibitory force feedback between a long toe flexor and the major ankle extensor muscles following spinal cord injury. Issue 8 (14th June 2020) - Niazi, Irrum F.; Lyle, Mark A.; Rising, Aaron; Howland, Dena R.; Nichols, T. Richard
Abstract: Inhibitory pathways from Golgi tendon organs project widely between muscles crossing different joints and axes of rotation. Evidence suggests that the strength and distribution of this intermuscular inhibition is dependent on motor task and corresponding signals from the brainstem. The purpose of the present study was to investigate whether this sensory network is altered after spinal cord hemisection as a potential explanation for motor deficits observed after spinal cord injury (SCI). Force feedback was assessed between the long toe flexor and ankle plantarflexor (flexor hallucis longus), and the three major ankle extensors, (combined gastrocnemius, soleus, and plantaris muscles) in the hind limbs of unanesthetized, decerebrate, female cats. Data were collected from animals with intact spinal cords (control) and lateral spinal hemisections (LSHs) including chronic LSH (4–20 weeks), subchronic LSH (2 weeks), and acute LSH. Muscles were stretched individually and in pairwise combinations to measure intermuscular feedback between the toe flexor and each of the ankle extensors. In control animals, three patterns were observed (balanced inhibition between toe flexor and ankle extensors, stronger inhibition from toe flexor to ankle extensor, and vice versa). Following spinal hemisection, only strong inhibition from toe flexors onto ankle extensors was observed independent of survival time. The results suggest immediate and permanent reorganization of force feedback in the injured spinal cord. The altered strength and distribution of force feedback after SCI may be an important future target for rehabilitation. Abstract : Golgi tendon organ pathways contribute to coordination of limb extensors during motor tasks including locomotion. Normally, these inhibitory force feedback pathways are flexibly weighted. We show that following spinal cord injury, force feedback is permanently reorganized. Balance is lost and biased inhibition emerges from toe flexors onto ankle extensors.